Cell Membrane Vesicles with Enriched CXCR4 Display Enhances Their Targeted Delivery as Drug Carriers to Inflammatory Sites. Issue 23 (23rd October 2021) - Wang, Dandan; Jiang, Shengjie; Zhang, Fengyi; Ma, Siqin; Heng, Boon Chin; Wang, Yuanyuan; Zhu, Junxia; Xu, Mingming; He, Ying; Wei, Yan; Zhang, Xuehui; Xia, Bin; et al.
Abstract: Cell membrane vesicles (CMVs) are composed of natural cell membranes which makes them effective drug delivery systems with low immunogenicity and prolonged circulation time. However, targeting delivery of CMVs in vivo for clinical applications is still a major challenge. In this study, CXCR4 recombinant lentivirus is transfected into MC‐3T3 cells and membrane CXCR4‐enriched MC‐3T3 cells are obtained. CMVs with enriched membrane CXCR4 display (CXCR4‐CMVs) are obtained from the transfected MC‐3T3 cells. Curcumin, an effective natural anti‐inflammatory compound, is encapsulated into CXCR4‐CMVs through physical entrapment (CXCR4/Cur‐CMVs), with the membrane integrity of CXCR4/Cur‐CMVs being well‐preserved. CXCR4/Cur‐CMVs induce enhanced M2 macrophage polarization, exhibit anti‐inflammatory effects, and significantly improve homing via the CXCR4/CXCL12 axis in vitro. Utilizing ulcerative colitis and apical periodontitis as inflammatory disease models, it is found that CXCR4/Cur‐CMVs are obviously aggregated within inflammatory areas after intravenous administration, which results in significant amelioration of ulcerative colitis and apical periodontitis. Therefore, this research may provide a feasible and innovative approach for fabricating an inflammatory site‐targeting delivery system, by engineering CMVs to increase membrane‐presenting CXCR4 receptor. Abstract : Effective inflammation‐targeting delivery for clinical applications is still a challenge. Cell membrane vesicles without (CMVs) and with enriched CXCR4 display (CXCR4‐CMVs) are fabricated. CMVs retain natural cell membrane structure and composition, which confers lower immunogenicity, prolonged circulation time, and enhanced targeting capacity. Curcumin is encapsulated within CXCR4‐CMVs (CXCR4/Cur‐CMVs), and the anti‐inflammatory and inflammation‐targeting effects of CXCR4/Cur‐CMVs are characterized.